Synthesis of Lignin Extracted from Black Liquor to Nano Porous Carbon Materials for Tetracycline Adsorption Application - Tassanai Tempiam; Anuchit Jaruvanawat; Atthapon Srifa; Worapon Kiatkittipong; Apiluck Eiad-Ua; Suttichai Assabumrungrat (My University, 2023)
Abstract Tetracycline is an antibiotic that suppresses the growth of bacteria, treats infections in the urinary tract, treats intestinal inflammation, bronchitis, treats dysentery, treats wounds, abscesses, pus, various inflammations due to infections. However, antibiotics have attracted extensive attention from the scientists because a variety of antibiotics have been. detected in soil, surface water, groundwater, and even in drinking water in the recent years. Antibiotics are among the most potent pollutants due to their overuse. This is because most antibiotics are metabolized and poorly absorbed by humans and treated animals, so many fractions are excreted through urine and feces into water. Therefore, it is urgent to remove tetracycline from water environment. There are several techniques used to remove tetracycline from aqueous solutions, coagulation, photo electrocatalytic degradation, ion exchange, membrane processing, and adsorption. Among them, adsorption is a widely used efficient technology, because it has the advantages of easy operation, low cost, high efficiency, and there is no risk of highly toxic by-products. In this work, lignin from black liquor in chemical pulping processes is used as a precursor for nano porous carbon synthesis. The physical and chemical properties of nano porous carbon was investigated by field-emission scanning electron microscope (FESEM), X-ray diffractometer (XRD), Energy Dispersive X-ray Spectroscopy (EDX), and Nitrogen sorption isotherm, respectively. The maximum surface area appears at 1,676.5 m 2 /g and a total pore volume of 1.091 cm 3 /g, this sample was used as an adsorbent and could perform its functions perfectly.
Keywords: Tetracycline antibiotics; Nanomaterials for catalytic reactions